Can a combination of interventions accelerate outcomes to deliver on the Sustainable Development Goals for young children? Evidence from a longitudinal study in South Africa and Malawi. (22nd December 2021) - Mebrahtu, Helen; Skeen, Sarah; Rudgard, William E.; Du Toit, Stefani; Haag, Katharina; Roberts, Kathryn J.; Gordon, Sarah L.; Orkin, Mark; Cluver, Lucie; Tomlinson, Mark; Sherr, Lorraine
Abstract: Background: This study aimed to identify possible entry points for interventions that can act as development accelerators for children and adolescents in South Africa and Malawi. Methods: This study was a secondary data analysis. Data were sourced from the Child Community Care longitudinal study which tracked child well‐being outcomes among 989 children (4–13 years) and their caregivers affected by HIV and enrolled in community‐based organizations in South Africa and Malawi. We examined associations between five hypothesized accelerating services/household provisions—measured as access at baseline and follow‐up and 12 child outcomes that relate to indicators within the Sustainable Development Goals (SDGs) framework. We calculated the adjusted probabilities of experiencing each SDG aligned outcome conditional on receipt of single, combined or all identified accelerators. Results: The results show household food security is associated with positive child education and cognitive development outcomes. Cash grants were positively associated with nutrition and cognitive development outcomes. Living in a safe community was positively associated with all mental health outcomes. Experiencing a combination of two factors was associated with higher probability of positive child outcomes. However, experiencing all three accelerators was associated with better child outcomes, compared with any of the individual factors by themselves with substantial improvements noted in child education outcomes. Conclusions: Combined delivery of specific interventions or services may yield greater improvements in child outcomes across different developmental domains. It is recommended that multiple support avenues in combination like improving food security and safe communities, as well as social protection grants, should be provided for vulnerable children to maximize the impact.